Beneficial action of resveratrol: How and why? - Diaz Gerevini, Gustavo Tomas (2016)
Flavonoid resveratrol modulates the transcription factor NF-κB; inhibits the cytochrome P450 isoenzyme CYP1 A1; suppresses the expression and activity of cyclooxygenase enzymes; and modulates Fas/Fas-ligand-mediated apoptosis, p53, mammalian target of rapamycin, and cyclins and various phosphodiesterases. This increases the cytosolic cAMP that activates Epac1/CaMKKβ/AMPK/SIRT1/PGC-1α pathway, which in turn facilitates increased oxidation of fatty acids, mitochondrial biogenesis, mitochondrial respiration, and gluconeogenesis. Resveratrol triggers apoptosis of activated T cells and suppresses tumor necrosis factor-α, interluekin-17 (IL-17), and other proinflammatory molecules, and thus is of benefit in autoimmune diseases. In addition, resveratrol inhibits expression of hypoxia-inducible factor-1α and vascular endothelial growth factor, explaining its effective action against cancer. Brain-derived neurotrophic factor (BDNF) that is involved in the pathogenesis of obesity, type 2 diabetes mellitus, and metabolic syndrome is also altered in depression, schizophrenia, bipolar disorder, and autism. We noted that BDNF protects against cytotoxic actions of alloxan, streptozotocin, and benzo(a)pyrene. Resveratrol prevents bisphenol A-induced autism, type 2 diabetes mellitus, and metabolic syndrome, suggesting that it may augment BDNF synthesis and action. We also observed that BDNF levels are low in type 2 diabetes mellitus and that BDNF enhances production of antiinflammatory lipid, lipoxin A4, whose levels are low in diabetes mellitus. Thus, resveratrol may augment production of lipoxin A4. Resveratrol alters gut microbiota and influences stem cell proliferation and differentiation. These pleiotropic actions of resveratrol may explain the multitude of its actions and benefits.